Pengaruh Pelatihan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Di PT United Tractors Tbk Cabang Banjarmasin - Saefuddin, Muhammad Yusuf Nur; Syarifuddin, Syarifuddin (eProceedings of Management, 2025)
AbstractThe purpose of this study is to determine the influence of job training and organizational culture on employeeperformance at PT United Tractors Tbk, Banjarmasin branch, as well as the impact of these factors on employeeperformance. This research is descriptive in nature and uses a quantitative methodology. A total of 40 staffparticipated in the saturated sampling technique. Data were analyzed using multiple linear regression analysis anddescriptive analysis. The analysis results indicate that employee performance, organizational culture, and job trainingare all very good. The results of the partial hypothesis testing show that although organizational culture has asignificant impact on employee performance, job training does not have a clear influence on personnel.Organizational culture and job training have a combined impact of 46.5%, while other factors contribute theremaining 53.5%.Keywords-job training, organizational culture, employee performance